Critical Aspects of the Professional Development of Higher Education Teachers - Fahara, Manuel Flores; Tobías, José Arturo Torres (American Journal of Education and Learning, 2019)
This study seeks to identify the critical aspects of professional development of higher education teachers from personal and professional expectations regarding their role at the different stages of their working career. The main objectives were to understand the professional development of higher education teachers, and to know what do they think and how do they live their practice, assuming that their activity has an impact on their professional identity as teachers, and that a continuous process of reflection and interpretation of their role could be helpful when dealing with educational changes. The research used a qualitative methodology of semi-structured interviews with a group of 18 teachers of a Mexican private university with a multi-campuses system. The general conclusion this study reaches is that the programs of professional development for higher education teachers must take into account their spatial and temporal context, and base their effectiveness on how it serves the needs and expectations of each teacher, which could vary in aspects like level of experience, area of professional expertise, learning style, and educational vision.